Immigrate/Imagine: Displacement as an Aesthetic Experience and Artistic-Pedagogical Impetus (TEL Tempo, Espaço e Linguagem, 2023)
Starting from the question of how visual arts relate to human displacement, we explore possible answers in its creative dimension - the production of artists - and its pedagogical dimension - art education. First, we define types of displacement and ways in which the displaced engage with reality. Then, drawing from the work of different artists and educators, we argue that displacement, whether due to personal motivation or external crises, can be an impulse for artistic creation, an aesthetic experience in itself, and can lead the displaced to reflections and learning. However, it is important to critically address the causes of displacement to avoid naive romanticization.Keywords: Visual Arts. Education. Human displacement.